Modelowanie rozprzestrzeniania zanieczyszczeń do powietrza atmosferycznego z projektowanej kompostowni osadów ściekowych = Modelling of the spread of pollutants in the air on the example of the proposed sewage sludge composting facility - Kołodziejczyk, Urszula; Czarna, Magdalena; Tarka, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A method of assessment of ambient air pollution due to sewage sludge composting activities. The assessment was done by identifying the sources of emissions, an indication of the types and amounts of pollutants from various sources and to determine the maximum concentrations of pollutants, and the frequency of crossing in relation to the reference value or maximum levels of substances in the environment.
Keywords: zanieczyszczenie powietrza; kompostownia osadów ściekowych; siarkowodór; amoniak; air pollution; composting plant; hydrogen sulfide; ammonium